Modernisasi Pelayanan Koperasi Dalam Upaya Meningkatkan Partisipasi Anggota Sebagai Pelanggan - Masrukhin, Masrukhin; Maryam, Siti (Koaliansi : Cooperative Journal, 2024)
The modernization of services brings positive benefits to the Public Service Business Unit at KPRI Hanukarya through the utilization of the latest technology. The store unit can provide better service to customers, for example, by offering digital payment options or mobile applications for online purchases, which in turn enhances the shopping convenience. Member participation also contributes significantly to the success of the cooperative, as members act both as owners and customers. As owners of the cooperative, members are expected to support the organization's management, particularly in terms of cooperative capitalization. The purpose of this study is to understand member participation in services, the modernization of cooperative services, and the efforts that must be undertaken to increase member participation in the Public Service Business Unit at KPRI Hanukarya. This research uses a case study method with descriptive quantitative analysis. Based on the results of the study, it was found that member participation in the volume of service utilization in the cooperative has declined from 2019 to 2022. However, the frequency of service utilization at the Public Service Business Unit remains high, where members often shop at the store unit during work breaks. On average, the number of members visiting the Public Service Business Unit in one day reaches around 200 people. The service modernization implemented at the Public Service Business Unit of KPRI Hanukarya received a score of "958", which falls under the "Good" category. To increase member participation as customers through the modernization of cooperative services, KPRI Hanukarya needs to improve stock checks and provide a greater variety of products, ensuring that members continue to use the services offered by the cooperative.